Peran GeoGebra dalam Menggeser Pembelajaran Geometri dari Hafalan Prosedural Menuju Pemahaman Konseptual - Dea Permata Sari; Arvin Efriani; Harisman Nizar (GEOMATH, 2026)
This study aims to develop exploration activities for flat shapes (triangles and quadrilaterals) using GeoGebra Classroom, designed to improve conceptual understanding among seventh-grade students. This research is motivated by the low understanding of mathematical concepts, where students often rely on procedural memorization. The study uses the Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), focusing on the Develop phase. Data collection instruments include expert validation sheets (content and media), field observation guidelines, and conceptual understanding tests. Data analysis is conducted using both qualitative and quantitative descriptive methods to assess the feasibility of the product. These exploration activities were intentionally designed without the instant presentation of formulas to encourage students to independently construct geometric properties through GeoGebra's dragging feature. The expected outcome of this research is the creation of a valid and practical learning tool that helps students visualize and understand geometric concepts meaningfully